The impact of identity politics on democracy and religious system in Indonesia - Utama, Sapta Baralaska; Tanasyah, Yusak (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2023)
Political identity in Indonesia has become an increasingly important issue in recent years. Ethnic, religious, and regional identities are often important factors in influencing people's political preferences. However, the impact of this political identity on Indonesia's democratic and religious system is debatable. The impact of political identity in Indonesia's democratic and religious system remains a complex and ever-changing issue. While some negative effects need to be addressed, political identity can also strengthen society and political participation. Therefore, continuous efforts are required to enhance the democratic and religious system in Indonesia and overcome conflicts arising from political identity.Â The purpose of this study is to clarify and analyze the impact of political identity on the democratic and religious system in Indonesia. This study aims to provide a better understanding of issues related to political identity and how these issues affect the political system and Indonesian society as a whole. Thus, this research is expected to contribute to the development of thoughts and policies related to the democratic and religious system in Indonesia.